Gambaran Perkembangan Elektrokardiografi pada Pasien Sindrom Koroner Akut di ICU RSI PK Muhammadiyah Pekajangan - Mas'ut, Ibnu; Sugiharto, S (Prosiding University Research Colloquium, 2022)
Background: Acute Coronary Syndrome (ACS) is a collection of disease processes that include unstable angina pectoris to Q wave myocardial infarction, caused by narrowing of the arteries due to the atherosclerosis process which is characterized by characteristic chest pain, changes in cardiac enzymes, and changes in electrocardiographic (ECG) images. . According to WHO (2017) 30% of deaths in the world are due to ACS. ECG is the main non-invasive investigation in establishing the diagnosis of ACS and evaluating the development of ACS itself. The purpose of the study: to determine the characteristics and descriptions of the development of the ECG in patients with acute coronary syndrome Methods: This study uses a retrospective descriptive research design, a documentation study with a total sample technique of 19 medical record data for ICU patients at RSI PKU Muhammadiyah Pekajangan for the period January 2019-December 2020. Results: The results of the medical record study of ACS patients mostly occurred in women (52.6%), the average occurred at the age of 61 years with an elementary school education of 57.9%, the average attack occurred 3.95 hours before entering the hospital, most of the first attacks (84.2%), mostly experienced in patients with hypertension 42.1%, with the ECG on the first day mostly ST elevation (68.4%) on the 2nd day there was a downward trend to 11 cases (57, 9%) ,10 cases (52.6%) on the 3rd day. and Isoelectric 1 case (5.3%). Conclusion: This study is expected to be a reference for hospitals to improve the improvement of ACS services in the ICU.